Situationally Selective Activation of Moral Disengagement Mechanisms in School Bullying: A Repeated Within-Subjects Experimental Study - Thornberg, Robert; Daremark, Elina; Gottfridsson, Jonn; Gini, Gianluca (Frontiers in Psychology, 2020)
With reference to social–cognitive theory, the aim of the present study was to examine whether school students’ tendency to display different moral disengagement mechanisms varies according to different social cues in hypothetical events in which they are engaged in bullying behavior. A repeated within-subjects experimental design was adopted. A total of 706 Swedish students (aged 10–20) from 75 classrooms responded to four verbal bullying vignettes by filling out a self-report survey. The results showed changes in moral disengagement mechanisms across the bullying situations. For instance, moral justification, victim blaming, and dehumanization scored higher in the mean victim condition and lower in the likable victim condition than in the other two conditions. Diffusion of responsibility was higher in the group conformity condition than in the other conditions. The findings also revealed differences in the levels of moral disengagement mechanisms within the bullying conditions. For example, euphemistic labeling and displacement of responsibility scored higher than the other mechanisms in the laughing audience condition. Victim blaming scored higher than the other mechanisms in the mean victim condition. Dehumanization, victim blaming, and moral justification scored lowest while euphemistic labeling was higher than most of the other mechanisms in the likable victim condition.